Pengaruh Antara Pemberian Fisioterapi Rutin Dan Neuromuscular Taping (NMT) Terhadap Penurunan Nyeri Pada Kasus Osteoarthritis Knee - Rosalina, Yanda; , Umi Budi Rahayu, S.Fis, M.Kes (2016)
Background: Osteoarthritis is a disorder characterized by progressive joint failure. Characterized by the breakdown of cartilage hyaline and growth of osteophytes at the joint. Clinical symptoms found in touch with pain. Transcutaneus Electrical Nerve Stimulation is an electrical stimulation is able to activate a large diameter nerve fibers that cause effect analgesic can reduce pain. Infra Red is electromagnetic radiation capable of causing vasodilation superficial tissues so as to reduce the pain. NeuroMuscular Taping a biomechanical therapy using decompression and compression to produce positive effects on the musculoskeletal system, neurology, vascular and lymphatic so as to reduce pain Objective: to find out the physiotherapy routine and NeuroMuscular Taping (NMT) to decrease pain in cases of osteoarthritis knee . Methods of study: This research is Quasi experimental pre and posttest with control group design research. The subject in this research is patients with osteoarthritis knee who were in Hospital Dr. Moewardi and Panti Wredha Dharma Bakti Surakarta. The amount of sample in this research is 20 samples. The statistic test will be used in Wilcoxon and Mann Whitney. The Result: the influence test use Wilcoxon for control group show the result p = 0,008 < 0,05 and in experiment group p = 0,005 < 0,05 the different influence test between control and experiment group use Mann Whitney show significant result 0,0001 which mean there are influence differences between control and experiment group.Conclusion: There is a difference of influence between of physiotherapy routine and NeuroMuscular Taping (NMT) in reducing pain in cases of osteoarthritis knee.